Pre-Service's Feedback during Microteaching Practicum in the Covid-19: A Narrative Study - Dewi Puspitasari; Rayinda Eva Rohmah (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Teacher’s reflection during the practice of microteaching has received enormous attention. However, specific studies concerning student’s reflection of other friend’s microteaching performances in the pandemic of Covid-19 are still in a small number. The present study explores how pre-service teachers narrated their feedback to the other pre-service teachers who performed teaching practice in the micro-teaching class. They captured their friends’ performances and delivered feedback based on the parameters of Bloom’s (1956) affective and psychomotor domains. The findings showed that in the affective domain, there were some positive and negative emotions that existed during the process, while in the psychomotor aspect, there were certain gestures, and all were related to the preservice teacher’s perception.